Flexibility of the burden of proof and the principle of procedural collaboration - Mendoza Meza, Liz (2021)
The purpose of this article is to reflect on the application of the burden of proof, provided in the Article 23 of the New Labor Procedure Law, in cases in which, the responsible part for producing the evidence provides for them, but, their results are insufficient to determine the facts that support the claim. From there, we intend to discuss the application of the principle of procedural collaboration, as a mechanism before the application of the rules of distribution of the burden of proof, to seek a rationally justified and controllable judgment.